Case report: Treatment of metastatic dedifferentiated chondrosarcoma with pembrolizumab yields sustained complete response - Singh, Amisha; Thorpe, Steven W.; Darrow, Morgan; Carr-Ascher, Janai R. (Frontiers in Oncology, 2022)
Dedifferentiated chondrosarcomas (DDCS) are aggressive tumors with poor outcomes. Treatment of localized DDCS is primarily surgical, though most patients present with unresectable or metastatic disease. Systemic treatment options for advanced DDCS are limited and the benefits of chemotherapy in this patient population remain controversial. Among other systemic therapy options, there is emerging clinical evidence to support the use of immunotherapy in patients with advanced DDCS. However, studies regarding the efficacy of immunotherapy in advanced DDCS are limited. Here, we present the case of a patient with metastatic, programmed death- ligand 1 (PD-L1) positive DDCS treated with pembrolizumab who showed a sustained complete response for 24 months after initiation of therapy. To our knowledge, this case represents one of few documented cases of metastatic chondrosarcoma with sustained response to immunotherapy. The impressive response seen with PD-L1 inhibition in our patient indicates that immunotherapy is a successful treatment option in a subset of DDCS patients, and further investigation is needed to identify potential responders to immunotherapy.